Elucidation of the binding mechanism of astragaloside IV derivative with human serum albumin and its cardiotoxicity in zebrafish embryos - You-Jiao Wu; Zhan-Hua Li; Jiu-Yan Li; Yan Zhou; Run-Yue Wang; Xiao-Yi Chen; Lin-Sen Qing; Pei Luo (Frontiers Media S.A., 2022)
LS-102 is a new derivative of astragaloside IV (AGS IV) that has been shown to possess potentially significant cardioprotective effects. However, there are no reports concerning its interaction with human serum albumin (HSA) and toxicology in vertebrates. The present investigation was undertaken to characterize the interaction of AGS IV and LS-102 with HSA using equilibrium dialysis and UHPLC-MS/MS methods, along with computational methods. Notably, the effects of AGS IV and LS-102 were studied in vivo using the zebrafish embryo model. Markers related to embryonic cardiotoxicity and thrombosis were evaluated. We showed that the plasma protein binding rate of AGS IV (94.04%-97.42%) was significantly higher than that of LS-102 (66.90%-69.35%). Through site marker competitive experiments and molecular docking, we found that AGS IV and LS-102 were located at the interface of subdomains IIA and IIIA, but the site I might be the primary binding site. Molecular dynamics revealed that AGS IV showed a higher binding free energy mainly due to the stronger hydrophobic and hydrogen bonding interactions. Moreover, the secondary structure implied no obvious effect on the protein structure and conformation during the binding of LS-102. LS-102 significantly ameliorated the astramizole-induced heart rate slowing, increased SV-BA spacing, and prevented arachidonic acid-induced thrombosis in zebrafish. To our knowledge, we are the first to reveal that LS-102 binds to HSA with reversible and moderate affinity, indicating its easy diffusion from the circulatory system to the target tissue, thereby providing significant insights into its pharmacokinetic and pharmacodynamic properties when spread in the human body. Our results also provide a reference for the rational clinical application of LS-102 in the cardiovascular field.